The Influence of Staff Competence on Performance of Procurement Contracts Management in Public Sector in Tanzania - MIHUNGO Sylvanus S.; MWAGIKE Leonarda (Ученые записки Института Африки Российской академии наук)
The study objective was to examine the influence of staff competence on performance of procurement contracts management in public sector. The study employed a case study design as a mechanism of resource allocation. The study targeted a total of 142 employees of TIB Development Bank Ltd which is a public bank operating in Tanzania. Stratified sampling technique was employed to select 85 employees. Data were collected from the sample through interview and questionnaire and then were analyzed using both descriptive statistics and inferential statistics while factor analysis was used to test the suitability of the data for analysis. Findings from Multiple regression indicated that staff competence (β1 = 0.279, p < 0.05) had a positive and significant influence on the performance of procurement contracts management. Additionally, the correlation revealed that staff competence is likely to strongly improve procurement contracts management performance. It is also vital for the organization to provide training to the staff so as to allow them to develop new skills and knowledge on procurement contracts management in order to improve the performance of such contracts.